Genetic diversity in Borrelia burgdorferi sensu lato - Ann-Kristin Tveten (Bioingeniøren, 2014)
Background: Borrelia burgdorferi sensu lato complex comprise a number of Borrelia species related to Lyme Borreliosis (LB). Three of the human pathogenic species, Borrelia burgdorferi sensu stricto, Borrelia afzelii and Borrelia garinii are common in Europe. Human LB infection is a complex disease and the different Borrelia species display different clinical manifestations.